2020
DOI: 10.1680/jenge.17.00033
|View full text |Cite
|
Sign up to set email alerts
|

Heat energy from a shallow geothermal system in Glasgow, UK: performance evaluation design

Abstract: This study reports on the actual energy and economic performance of a water source heat pump recently installed and operated at a Glasgow Subway Station using subsurface water ingress to provide heating and domestic hot water. This follows from a previous publication (Hytiris et al., 2016) that detailed the empirical measurements and design of a heating system designed on the basis of a fifteen-month monitoring period of the water flow and temperature. The perennial water flow at a relatively high temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The total energy consumption for the five radiators over that period was 0.904 MWh (0.904 MWh = 904 KWh/7 days = 129.14 KWh per day. 129.14 kWh/16 h = 8.07 KW) [9]. With the readings from the ASHP's energy monitoring system, it is concluded that the energy input for this station has been reduced by almost 70%.…”
Section: Results and Lessons Learntmentioning
confidence: 94%
See 3 more Smart Citations
“…The total energy consumption for the five radiators over that period was 0.904 MWh (0.904 MWh = 904 KWh/7 days = 129.14 KWh per day. 129.14 kWh/16 h = 8.07 KW) [9]. With the readings from the ASHP's energy monitoring system, it is concluded that the energy input for this station has been reduced by almost 70%.…”
Section: Results and Lessons Learntmentioning
confidence: 94%
“…Clean Technol. 2019, 2, 00 2 performances [8,9]. The latter study also highlighted the lessons learnt following installation and the potential for this system to be scaled up in similar environments.…”
Section: Ashp Installationmentioning
confidence: 80%
See 2 more Smart Citations
“…The station's old heating system was based 100% in electricity (electric fired radiators), consuming 10 kW without counting for the DHW. The WSHP requires a 4 kW input covering the DHW as well [10]. The payback period for this trial setup considering all the installation costs is projected to be 12 years.…”
Section: Heating System's Performancementioning
confidence: 99%